2013
DOI: 10.1002/gcc.22059
|View full text |Cite
|
Sign up to set email alerts
|

Frequent DNA methylation of MiR‐129‐2 and its potential clinical implication in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a highly malignant tumor with poor prognosis and high mortality due to a lack of effective medical treatment and apparent early stage symptoms. Understanding molecular mechanism of cancer development is crucial for HCC diagnosis, prognosis, and treatment. Recently, microRNAs have been shown to play an important role in carcinogenesis, being regulated by DNA methylation in several cases. In this study, a whole genome approach was used to identify methylation-regulated miRNAs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 19 publications
3
39
0
Order By: Relevance
“…miR-129 down-regulation is tightly associated with disease stages and progression, and its down-regulation is attributed to hypermethylation of its promoter (Yu et al, 2013). Similar down-regulation in miR-129 was also observed in hepatocellular carcinoma (Lu et al, 2013;Chen, et al, 2013). These results suggest that miR-129 plays a crucial role in tumorigenesis.…”
Section: Introductionsupporting
confidence: 54%
“…miR-129 down-regulation is tightly associated with disease stages and progression, and its down-regulation is attributed to hypermethylation of its promoter (Yu et al, 2013). Similar down-regulation in miR-129 was also observed in hepatocellular carcinoma (Lu et al, 2013;Chen, et al, 2013). These results suggest that miR-129 plays a crucial role in tumorigenesis.…”
Section: Introductionsupporting
confidence: 54%
“…One investigation showed that miR-129-2 was frequently hypermethylated in HCC cells and clinical samples, offering a potential methylation marker for HCC diagnosis [10]. Another study identified the down-regulated expression of miR-129-2 in HCC tissues in a manner reversely correlated with the level of miR-129-2 methylation.…”
Section: Dna Methylation and Mir-129 Expressionmentioning
confidence: 99%
“…Human miR-129-1 is among the seven miRNAs recognized in genomic regions near FRA7H, one of the fragile sites in chromosome 7q32 which is frequently deleted in some solid tumors [9]. MiR-129 family members are generally recognized as tumor suppressors with decreased expression in different tumors [10][11][12][13][14][15][16]. However, accumulating evidence indicates that miR-129 could play a dual role in tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, its potential utility as an early diagnostic marker for HCC was studied Lu et al, 2013).…”
Section: Mir-129-2mentioning
confidence: 99%